Improving the solubility of the antichagasic drug benznidazole through formation of inclusion complexes with cyclodextrins - José Lamartine Soares Sobrinho; Mônica Felts de La Roca Soares; Juan Jose Torres Labandeira; Lariza Darlene Santos Alves; Pedro José Rolim Neto (Química Nova, 2011)
This study describes unpublished research on improving the solubility of benznidazole by the formation of an inclusion complex. The cyclodextrins selected were αCD, βCD, γCD, HPβCD, RMβCD and SBβCD. All complexes were obtained in solution, presenting 1:1 stoichiometry according to the phase solubility diagram. The highest association constants were obtained with RMβCD and SBβCD, being selected for attainment of solid state complexes. These were characterized using XRD, SEM and dissolution test. The data obtained suggest the formation of complexes and indicate that these may provide a promising alternative way of developing solid doses of drug with suitable biopharmaceutical properties.